INSTRUCTIONAL COMPETENCIES OF MATHEMATICS TEACHERS AND THEIR PERFORMANCE IN THE EXECUTION OF TASK - Oriarte, Ronald; Molines, Eric; V. Taracina, Irene; A. Zamora, Daisy A. Zamora; Pańoso, Jenette; Rose M. Olea, Merry; Leo T. Olea, Wendell (IJBLE Scientific Publications Community Inc., 2023)
This study determined the instructional competencies of Mathematics teachers and their performance in the execution of tasks in Lopez East District. The study used the descriptive-evaluated-correlational method of research with documentary analysis in describing the effects of instructional competencies and performance of the teachers. Purposive sampling was used as the locale of the study. The statistical tools used were weighted mean, frequency count, percentage, rank order, Kendall Coefficient of Concordance, and its corresponding Chi-square test. The instructional competencies of the teachers were Very Much Evident. There is a significant agreement on the rank orders on the instructional competencies in terms of knowledge of subject matter, communication skills, instructional practices, evaluation, and professionalism and there is no significant agreement in terms of problem solving. The teachers’ performance in the execution of tasks was Outstanding. There is a significant agreement on the rank orders of the level of teacher’s performance. The result of this study was a great help to the learners and also to the teachers, as facilitators of learning, are encouraged to employ modern methodologies such as using computer-based resources in teaching. The researcher was motivated to assess the instructional competencies of Mathematics teachers and their teaching performance in Lopez East District.